(untitled) (Olhar de Professor, 2023)
This text aims to elucidate how the Neoliberal ideology has modulated a biased view of the BNCC, discussing the consequences of this with/in external and large-scale assessments. It seeks to answer the following questions: What are the BNCC’s relationships with external and large-scale assessment? How have these been configured as standardization in compliance with the Neoliberal ideology and what are its effects on materiality and school culture? To answer these questions, research and bibliographic analysis were carried out on the subject in question, adopting as main theoretical references Azevedo (1997), Peroni (2003), Gentili (1998), Lima and Sena (2020), Cássio (2019), Cury; Reis; Zanardi (2018), Dourado; Siqueira (2019), Oliveira (2018), Felipe (2020), Duarte (2001), Araújo (2004), Freitas (2012, 2018), Luckesi (2011), Sacristán (2017). It is concluded that the education imposed by the BNCC and the assessment made of it is not a transformative education, but a conformist education that meets the demands of the market.